Efficiency Analysis of Firm Financial Performance: Case Study of PT. Unilever Indonesia - Sumarti, Sumarti (EkBis: Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study is to analyze the profitability ratios and company liquidity ratios to assess the efficiency of company performance. This research is included in descriptive research, which is research that seeks to describe a phenomenon, event, event that is happening now. The reason this type of research is used is because the researcher tries to describe the events and events that are the center of attention without giving special treatment to those events. The study was conducted at PT. Unilever Indonesia, is the largest manufacturing company in Indonesia. The data analysis technique used in this study is quantitative descriptive using financial ratio analysis. The results show financial performance seen from the profitability ratio, overall the average is said to be efficient because of its magnitude above the industry average as a benchmark. Financial performance can be seen from the liquidity ratio, overall the average ratio is said to be liquid because the average is above the industry average as a benchmark.